Rejecting or Remaining? The Second Generation in the Unification Movement - Folk, Holly (Nova religio, 2025)
This article draws on the cohort theory of sociologist Karl Mannheim to consider the “second-generation issue” in the Unification movement. Mannheim’s understanding of the “problem of generations” was that generational cohorts have formative differences that create different visions for society. For new religious movements, these differences are often irreconcilable. In the international religious movement founded in Korea by Sun Myung Moon (1920–2012), Unification theology strongly shapes family life and parents’ expectations of children. Today, however, not only is the outmigration of young adults exceptionally high, in several countries Second-Generation individuals have publicly criticized both the Unification movement and their own families, sometimes calling for radical changes to laws governing children and religion. This article considers the internal and external pressures exacerbating intergenerational tensions within the Unification movement. The article concludes with an afterword in which the broader social implications from the case study of Unificationism are discussed.